Pengaruh Metode SAS (Struktural Analitik Sintetik) Terhadap Keterampilan Menulis Permulaan Pada Siswa Kelas II MIN Kota Medan - Masriana; Rambe, Riris Nurkholidah; Zunidar (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
The learning method is a way or technique of presenting learning materials that will be used by teachers when presenting learning materials, either individually or in groups. Effective and efficient learning methods can help students to learn well and achieve the educational goals that have been set. This research is motivated by the low writing skills of students due to the methods used are not optimal so that learning seems boring. The purpose of this study is to determine the effect of the SAS (Structural Analytical Synthetic) method on the initial writing skills of class II students of MIN Kota Medan. The type of research used is quantitative with an experimental type of research, with the research population being class II students of MIN 7 Kota Medan totaling 40 people. With a sample of class II A experimental class totaling 20 people and class II B control class totaling 20 people. Data collection was carried out through Pretest and Posttest questions. By using data analysis techniques namely Validity Test, Reliability Test, Difficulty Level Test, Discriminating Power, Data Normality Test, Variance Homogeneity Test, and Hypothesis Test. Based on the results of the research conducted by the researcher, it can be seen that there is a significant influence on the SAS (Structural Analytical Synthetic) learning method on the initial writing skills of class II students of MIN 7 Medan City. This is also proven by the results of the hypothesis test where the sig value (2-tailed) in the experimental class is 0.000 <0.05, meaning there is an influence on the treatment in the experimental class, so Ha is accepted and HO is rejected at the level of a = 0.05. Thus, it can be concluded that the SAS (Structural Analytical Synthetic) method has a significant influence in improving the initial writing skills of class II students of MIN 7 Medan City.